Eucalyptol ameliorates early brain injury after subarachnoid haemorrhage via antioxidant and anti-inflammatory effects in a rat model - Gang Xu; Junsheng Guo; Chunming Sun (Taylor & Francis Group, 2021)
Context As the terpenoid oxide extracted from Eucalyptus L. Herit (Myrtaceae), eucalyptol (EUC) has anti-inflammatory and antioxidant effects. Objective To evaluate the neuroprotective role of EUC in subarachnoid haemorrhage (SAH). Materials and methods Sprague-Dawley rats were divided into 4 groups: sham group, SAH group, SAH + vehicle group, and SAH + EUC group. SAH was induced by endovascular perforation. In SAH + EUC group, 100 mg/kg EUC was administrated intraperitoneally at 1 h before SAH and 30 min after SAH, respectively. Neurological deficits were examined by modified Neurological Severity Scores (mNSS). The brain edoema was evaluated by wet-dry method. Neuronal apoptosis was detected by Nissl staining. The expression of Bcl-2, cleaved caspase-3, phospho-NF-κB p65, ionised calcium-binding adapter molecule-1 (Iba-1), nuclear factor erythroid-2 (Nrf-2), and haem oxygenase 1 (HO-1) were measured by Western blot. Expression of pro-inflammatory cytokines was detected by qRT-PCR. Oxidative stress markers were also measured. Results EUC markedly relieved brain edoema (from 81.22% to 78.33%) and neurological deficits [from 16.28 to 9.28 (24 h); from 12.50 to 7.58 (48 h)]. EUC reduced neuronal apoptosis, microglial activation, and oxidative stress. EUC increased the expression of HO-1 (1.15-fold), Nrf2 (1.34-fold) and Bcl-2 (1.17-fold) in the rats' brain tissue, and down-regulated the expressions of cleaved caspase-3 (41.09%), phospho-NF-κB p65 (14.38%) and pro-inflammatory cytokines [TNF-α (34.33%), IL-1β (50.40%) and IL-6 (59.13%)]. Discussion and Conclusion For the first time, this study confirms that EUC has neuroprotective effects against early brain injury after experimental SAH in rats.